Evaluation of wildlife food plot seed mixes for Kansas - Tajchman, Alan J. (Kansas State University, 2015)
Three wildlife seed mixes were tested, Perfect Plot (BioLogic), Rack Force (Evolved Harvest), and Bird and Buck Whitetail and Gamebird mix (Star Seed). Two methods of research were conducted, (1) a food plot monitoring field study, and (2) a seed germination laboratory test. Food plots were planted in northwest (Jennings) and northeast (Manhattan) Kansas. Single season occupancy models from Program MARK were used to determine plot usage and preference of the seed mixes. Feeding patterns were analyzed from two locations targeting white-tailed deer (Odocoileus virginianus). Camera trap data were also analyzed for raccoon (Procyon lotor), wild turkey (Melagris gallopavo), and coyote (Canis latrans). During the summer 2014, the Bird and Buck mix retained the greatest amount of desirable vegetation, compared to the Rack Force and Perfect Plot mixes, which exhibited intermediate and relatively poor stand condition, respectively. White-tailed deer were documented at 100% occupancy using all (i.e., 100%) plots of all three mixes in Manhattan and Jennings, Kansas. In Manhattan, a significant increase in feeding events was observed for the months of July (45% of days) and August (50% of days) compared to the month of June (34% of days; p < 0.02). In contrast, deer feeding events in Jennings declined from 67% and 55% of days in June and July, respectively, to only 18% of days in August (p < 0.001). After initially having establishment issues among all three mixes, a laboratory study was initiated comparing the germination rates of each seed mix. Ten 1-gram random samples of each seed mix were tested in complete darkness at a constant 25-30°C for 25 days. When comparing daily germination rates of the seeds in the mixes, peak germination for all mixes (p < 0.0001) occurred on days 5-10 and 12-14. A single expected germination rate of similar plant types (i.e. alfalfa, clover, chicory, grasses) was computed from the seed tag, and then compared to the observed proportion of total seeds sampled that germinated. Bird and Buck recorded the highest germination, 79%, only 0.5% less than the expected overall germination. Perfect Plot and Rack Force recorded germination rates of 49% and 52%, which respectively, were 7% and 11% less than was expected.
Keywords: Food plots; Kansas; Odocoileus virginianus; Seed mix germination; Wildlife; White-tailed deer; Wildlife Conservation (0284); Wildlife Management (0286)